Guidelines for Selecting Aesthetic Procedures: A Comparison of Thread Lifting, Fillers, and Botox to Enhance the Quality of Aesthetic Clinics in Thailand - Thumtheang, Suttipong (Journal of Ecohumanism, 2025)
This academic article presents guidelines for selecting aesthetic procedures, including thread lifting, fillers, and Botox, to enhance the quality of aesthetic clinics in Thailand. It compares the advantages, disadvantages, and limitations of each procedure. Thread lifting is effective for skin tightening and collagen stimulation; however, its results are short-lived and require expertise from a qualified physician. Fillers provide immediate facial volume restoration and contouring but are costly and need to be reapplied every 6–18 months. Botox efficiently reduces wrinkles at a lower cost, but its effects last only 3–6 months, necessitating frequent treatments. The selection of each procedure should consider cost-effectiveness, safety, and customer satisfaction. Furthermore, training personnel and integrating technologies such as AI and CRM can enhance service efficiency and quality, ultimately improving client satisfaction and the credibility of aesthetic clinics.